Medicinal Plants in the Broad-Leaf Mixed Coniferous Forest of Tshothang Chiwog, Bhutan: Floristic Attributes, Vegetation Structure, Ethnobotany, and Socioeconomic Aspects - Jamba, Ngawang; Kumar, B. Mohan (Frontiers in Environmental Science, 2018)
The Himalayan Kingdom of Bhutan, located in one of the global biodiversity hotspots, is endowed with abundant floral wealth, including a wide array of medicinal plants (MPs). However, over-exploitation of these resources is widespread, and only a few studies have assessed the richness and diversity of Bhutanese forests and in particular about the MP resources. A vegetation survey was conducted in Tshothang Chiwog, south-eastern Bhutan to characterize the floristic structure of the broad-leaf mixed coniferous forests with a special focus on MPs. A questionnaire survey involving 40 farmers was also conducted to assess the ethnobotanical and socioeconomic aspects of MP extraction. A total of 157 plant species (38 trees, 19 shrubs, 85 herbs and ferns, and 15 climbers), representing 74 families and 137 genera were identified from the study area, of which 69 species (14 trees, 10 shrubs, 38 herbs and ferns, and seven climbers), belonging to 41 families and 69 genera were medicinally important. The most species-rich families of medicinal plants were: Asteraceae (eight spp.), Apiaceae (four spp.), Polygonaceae, Brassicaceae, Zingiberaceae, and Urticaceae (three species each). Herbaceous flora exhibited the highest diversity (Simpson diversity index (D) = 0.97 and Shannon-Weiner index (H’= 5.82) followed by trees and shrubs (viz. D= 0.95 and 0.92 and H’= 4.86 and 3.97 respectively). All but one herb showed abundance-to-frequency ratio (A/F) ≥0.05, signifying a contagious distribution pattern (large aggregated distribution). Girth class distribution of trees followed an inverse J-shaped pattern. Results of the ethnobotanic study documented 55 MPs. MP collection, as reported by the interviewees, generally improved the socioeconomic status of the local people of Tshothang Chiwog. Apart from improving the livelihood security of the local people, aspects relating to health care and culture are also important. Respondents were also concerned about the declining MP wealth of the Chiwog over the years due to over-exploitation. Monitoring the plant resources and adopting conservation programmes in the Chiwog, in their opinion, may improve the MP wealth of the locality. The lessons learned from the study may have applicability over the south-eastern part of Bhutan and other regions with similar eco-climatic features.